Improved Efficacy of Transcatheter Arterial Chemoembolization Using Warmed Miriplatin for Hepatocellular Carcinoma. (8th September 2014) - Yasui, Daisuke; Murata, Satoru; Onozawa, Shiro; Mine, Takahiko; Ueda, Tatsuo; Sugihara, Fumie; Kawamoto, Chiaki; Uchida, Eiji; Kumita, Shin-ichiro
Abstract : The aim of this study was to evaluate the efficacy and safety of transcatheter arterial chemoembolization (TACE) using warmed and nonwarmed miriplatin for hepatocellular carcinoma. Eighty patients (117 nodules), treated between January 2010 and June 2013, were evaluated. Thirty-two and 85 nodules were treated with nonwarmed and warmed miriplatin, respectively. The efficacy of TACE was evaluated on a per nodule basis according to treatment effect (TE). Adverse events were evaluated according to the Common Terminology Criteria for Adverse Events (CTCAE) v4.0. TE grades were significantly improved in the warmed group compared to the nonwarmed group (nonwarmed: TE 4, 12.5%; TE 3, 0%; TE 2, 15.6%; TE 1, 71.9%; warmed: TE 4, 34.1%; TE 3, 5.9%; TE 2, 9.4%; TE 1, 50.6%; P = 0.017 ) . Multivariate analysis revealed significant impact of warming miriplatin on objective response rate (odds ratio, 12.35; 95% confidence interval, 2.90–90.0; P = 0.0028 ). CTCAE grades of elevated aspartate and alanine transaminase after TACE were significantly higher in the warmed group (P = 0.0083 and 0.0068, resp.); however, all adverse events were only transient. The use of warmed miriplatin in TACE significantly improved TE without causing serious complications.